2019
DOI: 10.4103/jrms.jrms_704_18
|View full text |Cite
|
Sign up to set email alerts
|

Role of optical coherence tomography in the early detection of macular thinning in rheumatoid arthritis patients with chloroquine retinopathy

Abstract: Background: Chloroquine and hydroxychloroquine are drugs that are primarily used for the treatment of malaria and are also recommended for treating connective tissue disorders, autoimmune diseases, and some dermatological and inflammatory diseases. Treatment with these drugs has potential risk for the development of retinopathy, clinically characterized by bilateral pigment changes in the macula, as one serious ocular complication. The aim of this research was to evaluate the parafoveal and perifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…The localized thinning of retinal layers in the parafoveal region detected through OCT imaging confirms the early stage of toxicity before significant visual field loss was detected [82].…”
Section: Parafoveal Thinningsupporting
confidence: 55%
“…The localized thinning of retinal layers in the parafoveal region detected through OCT imaging confirms the early stage of toxicity before significant visual field loss was detected [82].…”
Section: Parafoveal Thinningsupporting
confidence: 55%
“…We further partitioned the OCTA images using different methods to provide more precise information and found that in the superficial retinal layers, the decrease in vessel density was mainly concentrated in the lower regions (IL, IR, I, and R) and near the foveal avascular zone (C1, C2, and C3), while in the deeper layers, the decrease in vessel density was more diffusely distributed (C1, C2, C3, C5, and C6). Most studies of chloroquine retinal toxicity have suggested that patients experience macular thinning, and Marija [28] found that this change was concentrated in the inferior, nasal, and temporal sectors. Lee [29] showed that the use of chloroquine led to a decrease in the thickness of the macular ganglion cell‐inner plexiform layer.…”
Section: Discussionmentioning
confidence: 99%
“…). Most studies of chloroquine retinal toxicity have suggested that patients experience macular thinning, and Marija [28] found that this change was concentrated in the inferior, nasal, and temporal sectors. Lee [29] showed that the use of chloroquine led to a decrease in the thickness of the macular ganglion cell-inner plexiform layer.…”
Section: And C6mentioning
confidence: 99%
“…Development of the optical coherence tomography in recent times has improved the ability to detect subtle early changes of retinal pathology such as thinning of the foveal photoreceptor outer segment, thickening of the retinal pigment epithelium, and loss of the macular ganglion cell–inner plexiform layer, and so on. However, with the advent of such sensitive screening techniques it is yet to be seen whether there are distinct improvements in the clinical outcomes 14,15. The risk of retinopathy is minimal when detected early; however, the prognosis declines sharply once the reduction in the central foveal thickness and classic bull’s-eye lesion are evident 13.…”
Section: Pharmacokinetics and Safetymentioning
confidence: 99%